The Analysis Study of Diagnosis and Surgical Management of Appendicitis:A Comprehensive Systematic Review - Jiwa Zhaqi Adiguna; Betti Merdiani Putri; Metti Herliani (International Medical Journal Corp. Ltd, 2025)
Introduction: Acute appendicitis (AA) is a prevalent cause of acute abdominal pain requiring emergency care. It poses a significant global healthcare burden, with a lifetime risk of 2–9%, peaking between ages 10 and 30. Complicated appendicitis accounts for 16–40% of cases, with a mortality rate of up to 5%. Advances in diagnosis and treatment, including imaging modalities and surgical techniques, have sparked debates on optimal strategies. Non-operative treatments like antibiotics are effective for uncomplicated cases but have recurrence risks, while complicated cases typically require surgical intervention. Methods: This systematic review adheres to PRISMA guidelines and evaluates studies from 2010–2024 on AA diagnosis and surgical management. Inclusion criteria encompass observational studies, RCTs, and cohort studies reporting diagnostic accuracy, surgical outcomes, and patient prognosis. Search strategies target databases like PubMed, Embase, Cochrane Library, and Scopus. Data extraction focuses on diagnostic methods, surgical techniques, and outcomes. Results: Preliminary findings from eight studies indicate varying outcomes based on diagnostic tools, surgical approaches (laparoscopic vs. open), and geographical practices. Complications, recurrence rates, and recovery times were analyzed to highlight trends and gaps in current knowledge. Conclusion: This review shows the importance of accurate, cost-effective diagnostic tools and tailored management strategies. Global variability in practices impacts outcomes, emphasizing the need for standardized protocols to optimize care and resource utilization in acute appendicitis management.